KAJIAN KESIAPAN PENERAPAN KONSEP KOTA KREATIF DESAIN DI SURAKARTA - Amesta Kartika Ramadhani; Soedwiwahjono Soedwiwahjono; Rufia Andisetyana Putri (Universitas Sebelas Maret Surakarta, 2015)
City plays important role making the city owns its high enchantment. This could effect on the emerging of city’s problems, where the city could not accommodate to all the complexity of people interest. Those problems need a new strategy to solve city’s problem which is more suitable to globalization era. The suitable solution is creative city which means city must be attractive by optimizing city’s local potentials. Surakarta, since 2013 has been established by the Ministry Of Tourism and Creative Economy of Indonesia to be a creative city of design by UCCN (UNESCO Creative City Network). There is much potency supporting Surakarta to be city of design. The existence of creative industries such as batik and furniture, various creative communities, creative spaces (Benteng Vastenburg, ISI, batik training organizations), and also various events based on cultural are good aspect to be considered. This research has purpose on knowing the readiness of Surakarta in implementing Creative City Of Design. The boundaries of this research are readiness of creative economy, readiness of creative community, readiness of creative space, readiness of leading, and readiness on holding events. This action then is followed by analyzing the readiness score of Surakarta as creative city of design. The research finding shows the readiness scales of Surakarta as creative city of design based on the five requirements that creative city must have. The research shows that Surakarta is not ready yet to be a creative city of design. There are some criterias that have not been accomplished. Creative economy, creative space, and experience in holding event are the lowest supporting aspect. Creative economy is the average in supporting creative city of design. Then the leading is the only one aspect who is ready in supporting implementation of Surakarta as city of design. Keywords: creative city, city of design